Brokering knowledge mobilization networks: Policy reforms, partnerships, and teacher education - Nicholas Ng-; Ruth Kane; Jesse Butler; Lisa Glithero; Rita Forte (Arizona State University, 2015)
Educational researchers and policy-makers are now expected by funding agencies and their institutions to innovate the multidirectional ways in which our production of knowledge can impact the classrooms of teachers (practitioners), while also integrating their experiential knowledge into the landscape of our research. In this article, we draw on the curriculum implementation literature to complicate our understandings of knowledge mobilization (KMb). Policy implementation, we suggest, can be understood as one specific type of KMb. We draw on different models for KMb and curriculum implementation and develop a relational model for KMb. Utilizing our model we critically reflect on the specific successes and challenges encountered while establishing, building, and sustaining the capacity of our KMb network. Our findings suggest that faculties of education are uniquely positioned to act as secondary brokers for the implementation of policy reforms within public education systems. To this end, we discuss how a relational KMb network is a "best practice" for establishing and sustaining partnerships among policy makers, educational researchers, and public school practitioners.